1991
DOI: 10.1210/endo-129-2-765
|View full text |Cite
|
Sign up to set email alerts
|

Antiprogesterone, RU 486, Facilitates Parturition in Cattle*

Abstract: RU 486, a potent progesterone antagonist with high affinity for progesterone receptor, was used alone or in combination with relaxin in late pregnant cattle to determine its effect on induction of parturition. Cross-bred beef cattle were bred by artificial insemination. An indwelling cannula was inserted into a jugular vein on day 269 (expected term = day 283) for repeated blood sample collection. On day 277, the cattle were assigned randomly to three groups (n = 6 each): group 1 received RU 486 (2 mg/kg BW, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
6
14
3
Order By: Relevance
“…The present study and other reports on endometrial expiants of nonpregnant sheep and endometrial epithelial cultures of cows (Horn et (Vallet et al, 1990;Larcher et al, 1995;Wathes et al, 1996b (Breton et al, 1996) (Vallet et al, 1990;Wathes et al, 1996b (Ledger et al, 1985;Li et al, 1991) and similar experiments with RU486 in rats showed that treatment resulted in an increase in uterine oxytocin receptor expression (Fang et al, 1996(Fang et al, , 1997. In the present study, disruption of the progesterone-dominated environment for as little as 4 h was sufficient to remove the inhibitory effect of progesterone.…”
Section: Progesterone Radioimmunoassaysupporting
confidence: 83%
“…The present study and other reports on endometrial expiants of nonpregnant sheep and endometrial epithelial cultures of cows (Horn et (Vallet et al, 1990;Larcher et al, 1995;Wathes et al, 1996b (Breton et al, 1996) (Vallet et al, 1990;Wathes et al, 1996b (Ledger et al, 1985;Li et al, 1991) and similar experiments with RU486 in rats showed that treatment resulted in an increase in uterine oxytocin receptor expression (Fang et al, 1996(Fang et al, , 1997. In the present study, disruption of the progesterone-dominated environment for as little as 4 h was sufficient to remove the inhibitory effect of progesterone.…”
Section: Progesterone Radioimmunoassaysupporting
confidence: 83%
“…Clinical observations indicated that dystocia was due to an insufficient myometrial activity and a poor widening of the posterior birth canal. In contrast to our study, no dystocia was observed after the induction of parturition in multiparous beef cows using mifepristone starting on day 277 (Li et al 1991), and the incidence was low in beef heifers (Dlamini et al 1995). The reason for this significant difference between these results is not clear but may be related to the time when antiprogestin treatment was started.…”
Section: Discussioncontrasting
confidence: 99%
“…The prepartal course of body temperature in D272CAp cows clearly resembles features described for the phase preceding normal term characterized by a transient decrease of 0.4 8C (48-22 h; Birgel et al 1994) and the absence of diurnal variation (48-8 h; Lammoglia et al 1997). The time between the onset of antiprogestin treatment and birth (48.7G7.5 h) is in the same range as reported after the initiation of parturition using the similar type antiprogestin, mifepristone, on days 277 and 278 in beef cows (55G3 h; Li et al 1991) or beef heifers (43G7 h; Dlamini et al 1995).…”
Section: Discussionsupporting
confidence: 63%
“…Ovarian production of progesterone is required to maintain pregnancy in cattle; ovariectomy causes an abrupt drop in circulating progesterone levels with abortion occurring in most cases (Tanabe 1966, Estergreen et al 1967, Chew et al 1979. Furthermore, the antiprogestin, RU 486, causes an abrupt decrease in progesterone and precisely induces premature parturition in cattle (Li et al 1991b). Although PRL secretion in cattle is tonically inhibited by the hypothalamus and remains significantly greater during the first 14 days after HST than seen in SOC animals, circulating PRL concentration gradually drifts lower but remains seasonally regulated (Benoit et al 1989, Cho et al 1998.…”
Section: Discussionmentioning
confidence: 99%